Sonic the hedgehog (2018), volume 3 ebook Battle for angel island. - Flynn, Ian (Sonic the Hedgehog (2018), 2020)
A powerful new foe has set his sights on Angel Island, and Sonic and his friends must defend it at all costs! When Neo Metal Sonic–an evil robot with Sonic's speed, Dr. Eggman's intellect, and an unbreakable mechanical body–conquers the island to grow his power even more, Sonic and his friends must team up and take the fight to him. But even with the full power of the Resistance behind him, will Sonic be able to take down Neo Metal Sonic once and for all? Collects Sonic the Hedgehog issues #9–12.